PATHOGENETIC MECHANISMS AND TREATMENT PRINCIPLES OF CHRONIC THROMBOEMBOLIC PULMONARY HYPERTENSION - N. A. Shostak; A. A. Klimenko; N. A. Demidova; I. V. Novikov (Рациональная фармакотерапия в кардиологии)
Data about chronic thromboembolic pulmonary hypertension (CTPH) prevalence is presented. The main CTPH clinical manifestations are described. The possible reasons and pathogenetic mechanisms of CTPH development are discussed. Features of unfavorable disease prognosis are also presented. Indications, results, limitations for CTPH surgical treatment are shown. Data of the currently completed clinical studies on bosentan, prostacyclin analogues and phosphodiesterase-5 inhibitors usage in CTPH are presented.